Kurikulum Pendidikan Pesantren: Mengurai Pembentukan Karakter Nasionalisme Santri - Halid, Ahmad (Universitas Muhammadiyah Jember, 2019)
The pesantren (Islamic boarding school) links yellow treatises to necessities of life, including enriching insights and broadening students' understanding of authoritative sources of Islamic teachings (al-qur'an and al-hadith) grounded in the thought of Muslim scholars; madzhab founders whose intellectual and personal values are widely recognized. This research aims to examine